An Analysis Of Code Mixing On Boy Williams Video Youtube Channel - Widyawati, Nurul (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research discusses about Code Mixing. The objectives of this research are to find out 1) The types of word the level of code mixing, 2) How types of levels are realized, 3) The reason for the use type of the levels code mixing. The research on this thesis was carried by using descriptive qualitative. The data were taken from Boy Williams video youtube channel. The result of this research show that were four types of code mixing based on word classes, such as Noun occurred 6 utterances, adjective occurred 3 utterances, verb occurred 2 utterances, and adverb occurred 1 utterances. This research found code mixing realized such as bilingualism, speaker and partner speaking (showing solidarity), and prestige. The last this research also found the reason why the type of the levels code mixing are realized because of special purposes . Sometimes the speakers used two or more language to state their through or message such as talking about particular topic there are 9 utterances, being emphatic about something there are 2 utterances, and repetition used for clarification there are 2 utterances. This research was expected to deliver an introduction about the code mixing for the people who read the research.